Improvement the Quality of Distributor Broiler Chickens Berkah Cahaya Mandiri Based on Customer Needs Analysis Using Integration Service Quality and Model Kano - Sarah Zafira Saweho*; Sari Wulandari; Muhammad Iqbal (Universitas Syiah Kuala, 2023)
Berkah Cahaya Mandiri is a family-owned business engaged in the poultry sector as a distributor of live broilers, which was established in 2018. This study aims to identify the attributes of customer needs obtained by extracting Voice of Customer (VoC) through in -depth interviews with seven Berkah Cahaya Mandiri customers. so that it can be used as a basis for service improvement. The method used to obtain the attributes of needs in accordance with customer preferences is Service Quality Integration and the Kano Model. Service Quality Integration and the Kano Model can complement the drawbacks of each method in solving problems by providing the right solution . The results of the integration of Service Quality and the Kano Model produce True Customer Needs. Based on True Customer Needs, there are 14 attributes that must be improved, namely the feasibility of delivery vehicles (TE1), the condition of the basket in good condition (TE5), employee friendliness in serving customers (EM1), employee courtesy in serving customers (EM2), ease of employees to contact (EM3), good communication skills with customers (EM4), timeliness of chicken delivery (RE1), the ability of distributors to fulfill demand (RE2), the quality of chicken is well maintained ( RE3), the suitability of chicken orders as promised (RE4), the ability of employees to handle customer complaints (RS3), the availability of compensation if the order is not as promised (AS1), weighing employees have good knowledge of chicken (AS2 ), the accuracy of calculating order payments (AS4).